A class of novel 4-DOF and 5-DOF generalized parallel mechanisms with high performance. (February 2018) - Jin, Xiaodong; Fang, Yuefa; Qu, Haibo; Guo, Sheng
Highlights: A new method for structural synthesis of the generalized parallel mechanisms is presented. The proposed method provides a way to integrate the well-known close-loop kinematic chains into parallel mechanisms. A class of 4-DOF and 5-DOF generalized parallel mechanisms is obtained. The proposed mechanisms possess the motion advantages of the close-loop kinematic chains and the traditional parallel mechanisms. Abstract: With the deepening and refinement of research, the traditional parallel mechanisms (PMs) have become increasingly hard to satisfy the demands of high rotational performance, decoupled motions, or some other specific motion properties. This paper focuses on the synthesis of a class of generalized parallel mechanisms (GPMs), which are capable of preserving the advantages and overcoming the shortcomings of the traditional PMs. Inspired by the closed-loop mechanisms with one or two dimensional high output performance and based on the characteristics of the set mapping and the group operations, a novel method about the synthesis of GPMs is proposed. By means of this method, a type of four degree of freedom (4-DOF) GPMs which contain 2T2R (T denotes a translational DOF and R represents a rotational DOF), 3T1R, and 1T3R categories are synthesized and further a kind of 5-DOF GPMs which are divided into 3T2R and 2T3R categories are obtained. The synthesis method is universal for the design of the GPMs and the proposed GPMs possess high performance because the articulated platforms are evolved from the well-known planar closed-loop linkage mechanisms.